2003
DOI: 10.1590/s0103-84782003000100018
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmose em ovinos e caprinos: estudo soroepidemiológico em duas regiões do Estado de Pernambuco, Brasil

Abstract: Com o objetivo de comparar variáveis epidemiológicas na toxoplasmose em ovinos e caprinos, amostras de soro de animais de propriedades localizadas em duas regiões do Estado de Pernambuco, Brasil, foram testadas pela reação de imunofluorescência indireta (RIFI) para detecção de anticorpos anti-Toxoplasma gondii. Dos 173 soros ovinos testados, em 35,3% foram encontrados resultados positivos, enquanto 40,4% dos 213 soros caprinos foram positivos à RIFI. Em ovinos, associações significativas foram encontradas para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
23
3
54

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 12 publications
14
23
3
54
Order By: Relevance
“…It is similar to that determined in the municipality of Goiânia (43.1%) 22 , in the microregion of Londrina (30.7%) 23 and in the States of Bahia (28.9%) 24 , Pernambuco (40.4%) 25 , Rio Grande do Norte (30.6%) 13 and Minas Gerais (45.8%) 7 . These results also diverge from other works conducted in São Paulo (14.5% 26 and 28.7% 14 ), Uberlândia (19%) 27 , Bahia (16.4%) 28 , Paraíba (24.5%) 29 and in Ceará (25.1%) 15 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It is similar to that determined in the municipality of Goiânia (43.1%) 22 , in the microregion of Londrina (30.7%) 23 and in the States of Bahia (28.9%) 24 , Pernambuco (40.4%) 25 , Rio Grande do Norte (30.6%) 13 and Minas Gerais (45.8%) 7 . These results also diverge from other works conducted in São Paulo (14.5% 26 and 28.7% 14 ), Uberlândia (19%) 27 , Bahia (16.4%) 28 , Paraíba (24.5%) 29 and in Ceará (25.1%) 15 .…”
Section: Discussionsupporting
confidence: 85%
“…In East Alagoas, the climate is humid, coastal and tropical and the mean annual temperature of around 25°C, typical of the Atlantic Forest, is propitious for the maintenance of oocysts of T. gondii, in agreement with results reported for the State of Pernambuco 25 , Brazil, which has a climate similar to Alagoas. Most notable are comparisons between the Zona da Mata in Pernambuco and the East region of Alagoas, where higher indices of seropositivity were registered for both.…”
Section: Conflict Of Interest Referencessupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, two reports suggested no correlation between gender and the presence of anti-T. gondii antibodies (Romanelliet al 2007, Caballero-Ortega et al 2008. The lack of association between seropositivity for T. gondii and herds with abortion problems was also reported by Soares et al (2009) and Silva et al (2003) in Brazil. However, all of the six farms in which reproductive problems had been reported, there were sheep seropositive to anti-T. gondii antibodies, suggesting that T. gondii could be the causative agent of the sporadic abortion reported by some farmers.…”
Section: Discussionmentioning
confidence: 95%
“…Seroprevalence rate of toxoplasmosis in northern and southern parts of Iran has been reported to be 55% and 22%, respectively (Assmar et al 1997). In Brazil, studies in flocks of small ruminants found prevalence rates of 21.4 to 92.4% of anti-T. gondii antibodies (Amaral et al 1978, Chiari et al 1987, Sella et al 1994, Gondim et al 1999, Silva et al 2003, Maciel & Araújo 2004, Motta et al 2008, Modolo et al 2008, Varaschin et al 2011. Despite the numerous publications on prevalence of antibodies against T. gondii in goats in different Brazilian regions there is only one report in Brazil reporting abortion by this parasite in goats, in the state of Rio Grande do Sul (Pescador et al 2007).…”
Section: Introductionmentioning
confidence: 99%